Determinants of consumers’ satisfaction and acceptance of direct selling - Alturas, B.; Santos, M. da C.; Pereira, I. (Proceedings of the Academy of Marketing Annual Conference 2005 - Marketing: Building Business, Shaping Society, 2005)
This paper studies the factors that influence the consumers’ satisfaction and acceptance of direct selling. Direct selling has been exhibiting in the last decade substantial growth in sales revenues and number of salespeople involved. Also the acceptance on the part of the consumers has been increasing; in spite of they show more and more demanding and informed. The literature reveals that the relationship between customer satisfaction and direct selling has not been sufficiently studied, yet. This paper, applying a quantitative approach attempts to provide some data on this relation. Results indicate that the consumer former experience is the major factor that leads to direct selling acceptance and satisfaction.